Removal of dyestuff from aqueous solution using layered double hydroxide / Siti Mariam Sumari - Sumari, Siti Mariam (Institute of Graduate Studies, UiTM, 2016)
Among the various techniques for colour removal, adsorption is the most efficient and practically viable. However due to the relatively high production cost and difficulty in regeneration of activated carbon conventionally used as adsorbent for dye removal, there is a need to find alternatives. Consequently, layered double hydroxide (LDH) was proposed as an alternative adsorbent. MgAl-NO3-layered double hydroxide (LDH) (molar ratio Mg/Al: 4:1) was synthesised using coprecipitation method followed by hydrothermal treatment at 70 oC. Its calcined form (CLDH) was obtained at calcination temperature of 500 oC. The physicochemical characteristics of adsorbents, LDH and CLDH were determined prior to adsorption study involving anionic dyes (Acid Blue 29, Reactive Black 5, Reactive Orange 16 and Reactive Red 120 and a cationic dye Methylene Blue. Physical characterization using XRay diffraction, FTIR spectroscopy, scanning electron microscopy (SEM) confirmed the identity of LDH and CLDH pertaining to d003 position, its functional groups and morphological features. Adsorption of anionic dyes were influenced by pH, adsorbent dosage, contact time, initial dye concentration and temperature. High percentage removal for anionic dyes was favoured at pH < pHpzc (9.3-10) indicating strong electrostatic interaction between negatively charged dyes and positively-charged surface of adsorbent. Complete decolorization of anionic dyes was achievable for 25 mg/L concentration within 3 hrs at 0.2 g/L LDH dosage, but higher dye concentration needed longer equilibrium time within 24 hours. Analysis of kinetic data using pseudo-first order (PFO), pseudo-second order (PSO) and intra-particle diffusion kinetic models revealed that PSO mechanism was predominant and the overall rate of dye adsorption process appeared to be controlled by more than one step….